qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
expand-arrow-icon
Relationship between roots and coefficients
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 4 x ^ { 2 } + 3 x - 22$
$y = 0$
$x$Intercept
$\left ( 2 , 0 \right )$, $\left ( - \dfrac { 11 } { 4 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 22 \right )$
Minimum
$\left ( - \dfrac { 3 } { 8 } , - \dfrac { 361 } { 16 } \right )$
Standard form
$y = 4 \left ( x + \dfrac { 3 } { 8 } \right ) ^ { 2 } - \dfrac { 361 } { 16 }$
$4x ^{ 2 } +3x-22 = 0$
$\begin{array} {l} x = 2 \\ x = - \dfrac { 11 } { 4 } \end{array}$
Find solution by method of factorization
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 22 } = 0$
$acx^{2} + \left(ad + bc\right)x +bd = \left(ax + b\right)\left(cx+d\right)$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 11 } \right ) = 0$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 11 } \right ) = \color{#FF6800}{ 0 }$
$ $ If the product of the factor is 0, at least one factor should be 0 $ $
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 11 } = \color{#FF6800}{ 0 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 11 } = \color{#FF6800}{ 0 } \end{array}$
$ $ Solve the equation to find $ x$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 4 } } \end{array}$
$\begin{array} {l} x = 2 \\ x = - \dfrac { 11 } { 4 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 22 } = \color{#FF6800}{ 0 }$
$ $ Divide both sides by the coefficient of the leading highest term $ $
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 4 } } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 2 } } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 4 } } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 2 } } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 2 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x + \dfrac { 3 } { 8 } \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 2 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x + \dfrac { 3 } { 8 } \right ) ^ { 2 } = \color{#FF6800}{ \dfrac { 11 } { 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x + \dfrac { 3 } { 8 } \right ) ^ { 2 } = \dfrac { 11 } { 2 } + \left ( \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$ $ When raising a fraction to the power, raise the numerator and denominator each to the power $ $
$\left ( x + \dfrac { 3 } { 8 } \right ) ^ { 2 } = \dfrac { 11 } { 2 } + \dfrac { \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 8 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 11 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 ^ { 2 } } { 8 ^ { 2 } } }$
$ $ Organize the expression $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 361 } { 64 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 8 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 361 } { 64 } }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 8 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 361 } { 64 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 8 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 361 } { 64 } } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 19 } { 8 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 8 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 19 } { 8 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 8 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 8 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 19 } { 8 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 8 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 19 } { 8 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 8 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 19 } { 8 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 8 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 19 } { 8 } } \end{array}$
$ $ Organize the expression $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 4 } } \end{array}$
$\begin{array} {l} x = 2 \\ x = - \dfrac { 11 } { 4 } \end{array}$
Calculate using the quadratic formula
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 3 \pm \sqrt{ 3 ^ { 2 } - 4 \times 4 \times \left ( - 22 \right ) } } { 2 \times 4 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 3 \pm \sqrt{ 361 } } { 2 \times 4 } }$
$x = \dfrac { - 3 \pm \sqrt{ \color{#FF6800}{ 361 } } } { 2 \times 4 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { - 3 \pm \color{#FF6800}{ 19 } } { 2 \times 4 }$
$x = \dfrac { - 3 \pm 19 } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } }$
$ $ Multiply $ 2 $ and $ 4$
$x = \dfrac { - 3 \pm 19 } { \color{#FF6800}{ 8 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 3 \pm 19 } { 8 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 3 + 19 } { 8 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 3 - 19 } { 8 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 19 } } { 8 } \\ x = \dfrac { - 3 - 19 } { 8 } \end{array}$
$ $ Add $ - 3 $ and $ 19$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 16 } } { 8 } \\ x = \dfrac { - 3 - 19 } { 8 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 16 } { 8 } } \\ x = \dfrac { - 3 - 19 } { 8 } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 2 } { 1 } } \\ x = \dfrac { - 3 - 19 } { 8 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 2 } { 1 } } \\ x = \dfrac { - 3 - 19 } { 8 } \end{array}$
$ $ Reduce the fraction to the lowest term $ $
$\begin{array} {l} x = \color{#FF6800}{ 2 } \\ x = \dfrac { - 3 - 19 } { 8 } \end{array}$
$\begin{array} {l} x = 2 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 19 } } { 8 } \end{array}$
$ $ Find the sum of the negative numbers $ $
$\begin{array} {l} x = 2 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 22 } } { 8 } \end{array}$
$\begin{array} {l} x = 2 \\ x = \color{#FF6800}{ \dfrac { - 22 } { 8 } } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = 2 \\ x = \color{#FF6800}{ \dfrac { - 11 } { 4 } } \end{array}$
$\begin{array} {l} x = 2 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 11 } } { 4 } \end{array}$
$ $ Move the minus sign to the front of the fraction $ $
$\begin{array} {l} x = 2 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 4 } } \end{array}$
$ $ 2 real roots $ $
Find the number of solutions
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 22 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 22 } \right )$
$D = \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } - 4 \times 4 \times \left ( - 22 \right )$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 9 } - 4 \times 4 \times \left ( - 22 \right )$
$D = 9 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 22 } \right )$
$ $ Multiply the numbers $ $
$D = 9 + \color{#FF6800}{ 352 }$
$D = \color{#FF6800}{ 9 } \color{#FF6800}{ + } \color{#FF6800}{ 352 }$
$ $ Add $ 9 $ and $ 352$
$D = \color{#FF6800}{ 361 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 361 }$
$ $ Since $ D>0 $ , the number of real root of the following quadratic equation is 2 $ $
$ $ 2 real roots $ $
$\alpha + \beta = - \dfrac { 3 } { 4 } , \alpha \beta = - \dfrac { 11 } { 2 }$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 22 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 4 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 22 } { 4 } }$
$\alpha + \beta = - \dfrac { 3 } { 4 } , \alpha \beta = \color{#FF6800}{ \dfrac { - 22 } { 4 } }$
$ $ Reduce the fraction $ $
$\alpha + \beta = - \dfrac { 3 } { 4 } , \alpha \beta = \color{#FF6800}{ \dfrac { - 11 } { 2 } }$
$\alpha + \beta = - \dfrac { 3 } { 4 } , \alpha \beta = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 11 } } { 2 }$
$ $ Move the minus sign to the front of the fraction $ $
$\alpha + \beta = - \dfrac { 3 } { 4 } , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 2 } }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo